Peningkatan Hasil Belajar Pada Pembelajaran Tematik Terpadu Menggunakan Model Think Pair Share di Sekolah Dasar - Purwanti, Yekti; Abidin, Zainal (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2021)
This study aims to describe student learning outcomes in integrated thematic learning using the think pair share cooperative model in class V SDN 08 Koto Gadang, IV Koto District. This type of research is a classroom action research using qualitative and quantitative approaches. The subjects in this study were teachers and students of grade V where there were 11 male students and 13 female students. The results showed that a) planning cycle I obtained a value of 84.08% with good qualifications increased in cycle II to 93.18% with very good criteria, b) the implementation of learning aspects of the first cycle teachers got a score of 81.24% with good qualifications increased in cycle II it becomes 93.75% with very good qualifications, while the aspects of students in cycle I get a value of 79.68% with good qualifications increasing in cycle II to 93.75% with very good qualifications, c) student learning outcomes in cycle I obtained an average value of 76.29 then increased in cycle II to 83.2 with a percentage of 87.5% completeness. Based on the research results, it can be concluded that the cooperative model of think pair share type can improve student learning outcomes in integrated thematic learning in class V SDN 08 Koto Gadang, IV Koto District.